International Anarchy Reconsidered:: Hobbes and International Relations - Balatsos, Konstantinos (Dia-noesis: A Journal of Philosophy, 2024)
Hobbes has been regarded as a core figure of IR theory by political theorists and international relations scholars. However, against delusive interpretations of his political philosophy, I will reexamine in this essay the notion of international anarchy and the place of it in the Hobbesian corpus, focusing mainly on chapter 13 of Leviathan. My point is that both the Realist and Rationalist schools overlook central features of Hobbesian political philosophy and draw a somehow misleading picture of what Hobbes truly said with regard to interstate relations and the state of nature.